2020
DOI: 10.5430/ijh.v6n1p63
|View full text |Cite
|
Sign up to set email alerts
|

Global policies on assistive robots for care of the elderly: A scoping review

Abstract: The elderly are the fastest growing portion of the world population. The majority of elderly want to remain independent as long as possible, with responsibility for their care often falling to family or caregivers. Assistive robots could help maintain independence in the elderly while relieving the burden of care on families and healthcare professionals. This scoping review seeks to examine the type and scope of global policies on the use of robotic technology for care of the elderly in international jurisdict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Consistent with this, participants in a study by Hoppe et al [ 51 ] showed a preference for a caregiver robot when asked to choose between a human and a robotic caregiver for assistance in daily living. When evaluating findings about perceptions and attitudes toward the specific use of assistive robots for the elderly, however, Plaschka et al [ 36 ] found very mixed reactions, with only one of the studies included in their scoping review finding no overall negative attitude toward or rejection of assistive and care robots. While such studies’ participants perceived reduced dependence on caregivers or family members (and, thus, increased autonomy for elderly robot users) as positive, negative responses often related to safety concerns, privacy or responsibility issues, and ethical considerations [ 36 , 52 ].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this, participants in a study by Hoppe et al [ 51 ] showed a preference for a caregiver robot when asked to choose between a human and a robotic caregiver for assistance in daily living. When evaluating findings about perceptions and attitudes toward the specific use of assistive robots for the elderly, however, Plaschka et al [ 36 ] found very mixed reactions, with only one of the studies included in their scoping review finding no overall negative attitude toward or rejection of assistive and care robots. While such studies’ participants perceived reduced dependence on caregivers or family members (and, thus, increased autonomy for elderly robot users) as positive, negative responses often related to safety concerns, privacy or responsibility issues, and ethical considerations [ 36 , 52 ].…”
Section: Related Workmentioning
confidence: 99%
“…When evaluating findings about perceptions and attitudes toward the specific use of assistive robots for the elderly, however, Plaschka et al [ 36 ] found very mixed reactions, with only one of the studies included in their scoping review finding no overall negative attitude toward or rejection of assistive and care robots. While such studies’ participants perceived reduced dependence on caregivers or family members (and, thus, increased autonomy for elderly robot users) as positive, negative responses often related to safety concerns, privacy or responsibility issues, and ethical considerations [ 36 , 52 ]. The latter include concerns that care robots could socially isolate older people, limit their self-determination, threaten their self-efficacy, objectify them, deprive them of social recognition, and violate their dignity [ 11 , 14 , 23 , 52 , 53 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation